BIG DATA, DATA SCIENCE AND MACHINE LEARNING AS THE LATEST MODERN TRENDS - Каримова Лайло Рахимбергановна (Journals Park Publishing, 2024)
This scientific article examines such important areas of IT – Information technologies as Big Data, Data Science and Machine Learning. Also, everything is supported by examples in various IT companies and not only. The results are summarized and the possibilities of further application in the near future are described.
Keywords: Big Data, Data Science, Data Scientist, Machine Learning, Artificial Intelligence, IT, Neural Networks, Big Data, Data Science, Machine Learning, Artificial Intelligence.